Trust, Sharia Compliance, and Technology Quality as Drivers of Digital Financial Innovation Adoption: Evidence from Bank Syariah Indonesia - Sukron Arifin; Naufal Rafi Widodo; Rizqi Ridlo Amanah (CV. Visionary Raya Sakti, 2026)
Purpose: This study aims to analyze the influence of trust, sharia compliance, and technology quality on the adoption of digital financial innovation at Bank Syariah Indonesia (BSI) Purworejo Branch. The research is motivated by the relatively low adoption rate of digital Islamic banking services in non-metropolitan areas, despite digital transformation being a strategic priority in the development of Indonesia’s Islamic financial industry. Design/methodology/approach: A quantitative approach with a correlational research design was employed. Data were collected from active users of the BYOND by BSI application selected through purposive sampling. Statistical analysis was conducted using multiple linear regression to examine both partial and simultaneous effects of the independent variables on digital innovation adoption. Findings: The findings reveal that trust, sharia compliance, and technology quality simultaneously have a positive and significant effect on the adoption of digital financial innovation. Partially, all variables significantly influence adoption, with trust emerging as the most dominant factor. These results indicate that religious-based trust plays a more substantial role than purely technical considerations in shaping customers’ adoption behavior in Islamic digital banking services. Research implications: Theoretically, this study strengthens and extends the Technology Acceptance Model (TAM) by integrating a spiritual and sharia-compliance dimension within the Islamic finance context. Practically, the findings encourage BSI to enhance contract transparency, strengthen digital sharia literacy programs, and improve customer data protection systems. Future research is recommended to adopt the Diffusion of Innovations (DoI) framework to further examine the broader dissemination process of digital sharia innovation across diverse regional contexts.